Deposition of Micro-elements through Leaf Fallen from Different Types of Vegetation, North-eastern Mexico - Dominguez-Gomez, Tilo G.; Gonzalez-Rodriguez, Humberto; Cantu-Silva, Israel; Ramirez-Lozano, Roque G.; Gomez-Meza, Marco V.; Socorro Alvarado, Maria Del (International Journal of Bio-resource and Stress Management, 2014)
The aim of the study was to determine monthly (2007) the content and deposition of Cu, Fe, Mn and Zn in leaf fallen litterfall samples collected in four sites, northeastern Mexico. Site 1 was located at 1600 m of altitude in a pine forest, mixed with deciduous trees; site 2 was at 550 m in the ecotone of a Quercus spp. forest and submontane scrub; sites 3 and 4 (at 350 m and at 300 m, respectively) were located in the Tamaulipan Thornscrub vegetation. Leaf fallen litterfall samples at each site (2,500 m2) were obtained from ten canisters of 1.02 m that were randomly situated at each site. The Cu annual deposition (g ha-1 yr-1) was significantly different among sites being higher in site 4 (23.2) and lower in site 1 (4.1). Fe deposition was also significantly higher in site 4 (522.2) and lower in site 1 (120.0). Mn was higher in site 2 (479.4) and lower in site 1 (64.6). Zn was significantly higher in site 1 (62.8) and lower in site 1 (24.3). Micronutrient annual order deposition was as follows: Fe>Mn>Zn>Cu. Differences in deposition may be attributable to environmental conditions and plant species composition at each studied plant community.